2012
DOI: 10.1016/j.yjmcc.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae create local signalling domains through their distinct protein content, lipid profile and morphology

Abstract: Compartmentation of signalling allows multiple stimuli to achieve diverse cellular responses with only a limited pool of second messengers. This spatial control of signalling is achieved, in part, by cellular structures which bring together elements of a particular cascade. One such structure is the caveola, a flask-shaped lipid raft. Caveolae are well-recognised as signalosomes, platforms for assembly of signalling complexes of receptors, effectors and their targets, which can facilitate efficient and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 122 publications
(201 reference statements)
1
67
1
Order By: Relevance
“…Increased osmotic stress greatly changed the release of Ca 2ϩ with G␣ q /PLC␤ stimulation (12,29). In unstimulated A10 cells, we found that lowering the osmolarity does not affect the basal Ca 2ϩ levels and in contrast to previous reports showed that osmotic stress increases external Ca 2ϩ leakage (29), suggesting that leakage may be cell-specific.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Increased osmotic stress greatly changed the release of Ca 2ϩ with G␣ q /PLC␤ stimulation (12,29). In unstimulated A10 cells, we found that lowering the osmolarity does not affect the basal Ca 2ϩ levels and in contrast to previous reports showed that osmotic stress increases external Ca 2ϩ leakage (29), suggesting that leakage may be cell-specific.…”
Section: Discussioncontrasting
confidence: 66%
“…On the cellular level, caveolae are thought to play a role in endocytosis and trafficking (10), although this has been disputed (11). Caveolae can also serve as a platform to organize and corral signaling molecules such as the ones involved in nitric oxide production (8,12). Early studies of caveolae postulated that they can play a role in mechanosensing, and the high density of caveolae in cells that undergo mechanical stress supported this idea.…”
mentioning
confidence: 99%
“…The basis for this difference is unclear, with all studies using isolated perfused rodent hearts and similar ranges of M␤CD concentration. However, repression of contractile function is consistent with the significant influences of membrane cholesterol and caveolae on a variety of ion channels, receptor function and signaling, and other physiological processes (3,4,13,22).…”
Section: Discussionsupporting
confidence: 56%
“…We propose that these interactions occur in caveolae of the invadopodial compartment and are responsible for an increased ECM degradative activity. Indeed, caveolae are membrane domains that 'build' protein-protein signalling complexes (Harvey and Calaghan, 2012) that are required for both invadopodia formation and ECM degradative activity (Caldieri et al, 2012;Caldieri et al, 2009;Yamaguchi et al, 2009). As such, caveolae could be a signalling platform in invadopodia for Na V -and NHE-1-dependent cancer cell invasiveness.…”
Section: Resultsmentioning
confidence: 99%